Effects of N-(2-propylpentanoyl) urea on nmda receptor subtype NR1A/NR2B Expressed in xenopus laevis oocytes - Penphimon Ponsup (Chulalongkorn University, 2012)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 2003